1980
DOI: 10.1002/dev.420130202
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in open‐field behavior as a function of age

Abstract: Male and female rats were observed in an open field at 30, 45, 60, 90, and 120 days of age. Thirty- and 45-day-old rats of both genders presented similar defecation, ambulation, and rearing scores. From 60 days on the male rats showed higher defecation scores and less ambulation and rearing than did the females. The gender difference observed in the adult rats reflected a decrease of defecation by females and a decrease of ambulation and rearing by males when compared to the earlier ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
27
4
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 6 publications
10
27
4
1
Order By: Relevance
“…The lack of significant and direct sex difference in EPM and open field behaviour is in accordance with the literature where such differences had not been reported before PND 60 (Masur, Schutz, and Boerngen 1980;Imhof et al 1993). Nevertheless there was a trend in that females showed more vertical exploration.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of significant and direct sex difference in EPM and open field behaviour is in accordance with the literature where such differences had not been reported before PND 60 (Masur, Schutz, and Boerngen 1980;Imhof et al 1993). Nevertheless there was a trend in that females showed more vertical exploration.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, although in the light males spent slightly more time in the inner circle than females (see Figure 2), males spent relatively even more time in the inner circle than females in the dark. Thus, although the light data showed trends conforming to previous literature reporting that males are more cautious and fearful than females [15,19,30], it seems odd that males should be relatively even more fearful than females in the dark. However, there may be another contributor to the differences in male and female open field behavior.…”
Section: Sex Differencessupporting
confidence: 82%
“…Lastly, Fan et al (2011) reported that nLPS (P5) male and female rats on P21 showed anxiolytic effects (spent more time in the open arms) on the EPM compared to nSal controls (Fan et al, 2011). The anxiolytic effects observed have been previously seen by others (Imhof et al, 1993;Masur et al, 1980;Walker et al, 2004).…”
Section: Neonatal Effects-existing Literature On the Effects Of Neonamentioning
confidence: 53%